PENGARUH PENERAPAN METODE SIMAK TERKA TERHADAP HASIL BELAJAR BAHASA INDONESIA MATERI TEKS DESKRIPSI PESERTA DIDIK KELAS II, SDN NO. 125 INPRES BULUKUNYI KAB. TAKALAR - Djafar, Hamsiah; Rosdiana; Sikki, Fitri (Department of Islamic Education Management, 2024)
This research was conducted with the main aim of evaluating the impact of applying the guessing method on Indonesian language learning outcomes, especially in the context of descriptive text material. In order to achieve this aim, this research adopted a quantitative approach using a pre-experimental design, one group pretest posttest. Participation involved all class II students, totaling 23 people, as the study population. Data analysis shows that there is a significant difference between learning outcomes before and after implementing the guessing method. Previously, the average learning outcome was 40.78, which was in the medium category, but after implementing this method, the average score increased to 74.87, which was in the high category. The results of the hypothesis test firmly strengthen the finding that the difference between the pre-test and post-test scores is significant. Analysis techniques, both descriptive and inferential, consistently support the conclusion that the application of the listening guess method has a real positive impact on Indonesian language learning outcomes among class II students. These findings provide an indication that the listening guess method can be considered an effective alternative in increasing students' understanding of descriptive text material.